14 The use of prehospital 12-lead electrocardiograms in acute stroke patients. (16th April 2018) - Munro, S; Cooke, Debbie; Joy, Mark; Quinn, Tom
Abstract : AIM: Emergency medical services (EMS) play a vital role in the recognition, management and transportation of acute stroke patients. UK guidelines recommend clinicians consider performing a prehospital 12-lead electrocardiogram (PHECG) in patients with suspected stroke, but this recommendation is based on expert consensus, rather than robust evidence. The aim of this study was to investigate the association between PHECG and modified Rankin scale (mRS). Secondary outcomes included in-hospital mortality, EMS and in-hospital time intervals and rates of thrombolysis received. Method: A multicentre retrospective cohort study was undertaken. The data collection period spanned from 29/12/2013 – 30/01/2017. Participants were identified through secondary analysis of hospital data routinely collected as part of the Sentinel Stroke National Audit Programme (SSNAP) and linked to EMS clinical records (PCRs) via EMS incident number. Results: PHECG was performed in 558 (48%) of study patients. PHECG was associated with an increase in mRS (aOR 1.44, 95% CI: 1.14 to 1.82, p=0.002) and in-hospital mortality (aOR 2.07, 95% CI: 1.42 to 3.00, p=0.0001). There was no association between PHECG and administration of thrombolysis (aOR 0.92, 95% CI: 0.65 to 1.30, p=0.63). Patients who had a PHECG recorded spent longer under the care of EMS (median 49 vs 43 min, p=0.007). No difference in times to receiving brain scan (Median 28 with PHECG vs 29 min no PHECG, p=0.14) or thrombolysis (median 46 min vs 48 min, p=0.82) were observed. Conclusion: This is the first study of its kind to investigate the association between PHECG and functional outcome in stroke patients attended by EMS. Although there are limitations in regard to the retrospective study design, the findings challenge current guideline recommendations regarding PHECG in patients with acute stroke. Conflict of interest: None Funding: University of Surrey School of Health Sciences PhD scholarship.